Shoulder injury related to vaccine administration and a growing challenge: a focused review - Pettyjohn, E. W.; Clugston, J. R.; Zaremski, J. L. (Current Sports Medicine Reports, 2022)
Shoulder injury related to vaccine administration (SIRVA), an entity that causes acute shoulder pain and may limit range of motion (ROM) after vaccination, is a condition where a small but significant percentage of patients are experiencing in light of the current push for mass immunizations against SARS-CoV-2 worldwide. A search of literature related to SIRVA was performed across multiple electronic databases. Women, patients reporting vaccine injection location to be too high, and patients without prior history of shoulder pain were the most common historical factors in those experiencing SIRVA. Tenderness to palpation and limited shoulder ROM were the most associated physical examination findings. When using magnetic resonance imaging, tendinopathy, subacromial-subdeltoid bursitis, and rotator cuff tears (partial or complete) were the most common findings. Radiographic imaging rarely aided the diagnosis. SIRVA is an entity that health care providers should be aware of to improve the care of patients that may experience these symptoms after vaccine administration.